2022
DOI: 10.3389/fonc.2021.827625
|View full text |Cite
|
Sign up to set email alerts
|

Derived Neutrophil-to-Lymphocyte Ratio Predicts Pathological Complete Response to Neoadjuvant Chemotherapy in Breast Cancer

Abstract: BackgroundDerived neutrophil-to-lymphocyte ratio (dNLR) is a biomarker associated with clinical outcome in breast cancer (BC). We analyzed the association of dNLR with pathological complete response (pCR) in triple-negative BC (TNBC) patients receiving neoadjuvant chemotherapy (CT).MethodsThis is a retrospective analysis of two randomized studies involving early stage/locally advanced TNBC patients receiving anthracycline/taxane-based CT+/−carboplatin (GEICAM/2006-03) or nab-paclitaxel/paclitaxel followed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…32 When specific subsets of BC were explored, NLR provided additional information regarding the likelihood of obtaining a pCR to NAC in postmenopausal Luminal B/HER2positive 33 and triple-negative BC. 34 Studies on other blood cell ratios such as platelet to lymphocyte ratio and monocyte to lymphocyte ratio showed conflicting results about their value as a predictive and/or prognostic factor and there are conflicting reports about which index provides the best prediction for the efficacy of NAC in BC. 35 However, it has been hypothesized that the combination of multiple biomarkers could better define the patients' inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…32 When specific subsets of BC were explored, NLR provided additional information regarding the likelihood of obtaining a pCR to NAC in postmenopausal Luminal B/HER2positive 33 and triple-negative BC. 34 Studies on other blood cell ratios such as platelet to lymphocyte ratio and monocyte to lymphocyte ratio showed conflicting results about their value as a predictive and/or prognostic factor and there are conflicting reports about which index provides the best prediction for the efficacy of NAC in BC. 35 However, it has been hypothesized that the combination of multiple biomarkers could better define the patients' inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…Another subsequent meta-analysis on 19 studies, con rmed this result (OR 1.6, 95% CI, 1.2-2.1, I 2 66%, p > 0.001) 30 . When speci c subsets of BC were explored, NLR provided additional information regarding the likelihood of obtaining a pCR to NAC in postmenopausal Luminal B/HER2 positive 31 and in triple negative BC 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In NSCLC patients treated with ICIs, high dNLR was associated with poorer PFS (HR = 1.56; p < 0.0001) and OS (HR = 2.02; p < 0.0001) [ 36 ]. A study including 308 patients with early/locally advanced TNBC explored the relationship between dNLR and pCR and found that a high dNLR at baseline might be associated with a lower pCR rate [ 37 ]. Similarly, this study found that patients with lower dNLR had longer PFS and OS.…”
Section: Discussionmentioning
confidence: 99%